The use of Botulinum toxin‐A injection for facial wrinkles: a histological and immunohistochemical evaluation. (27th April 2015) - El‐Domyati, Moetaz; Attia, Sameh K.; El‐Sawy, Ashraf E.; Moftah, Noha H.; Nasif, Ghada A.; Medhat, Walid; Marwan, Belkais
Summary: Botulinum toxin (BTX)‐A has been used for years in the reduction of facial wrinkles; however, histological and immunohistochemical changes after its use were not previously investigated. To evaluate histological and immunohistochemical changes after BTX‐A injection for facial wrinkles, sixteen volunteers, with wrinkles on the upper third of the face, were subjected to single injection of BTX‐A. Skin biopsy specimens were obtained from peri‐orbital wrinkle site (crow's feet area) before and after 3 months of BTX‐A injection. Using histological and immunohistochemical evaluation coupled with computerized morphometric analysis, measurement of epidermal thickness, wrinkle depth and width as well as quantitative evaluation of collagen types I and III and elastin was performed for skin biopsies. After BTX‐A injections, there were significant increase in wrinkle width and granular layer thickness ( P < 0.001), while the other histometrical measures as well as the immunohistochemical expression of collagen types I and III and elastin showed no significant difference ( P > 0.05). However, collagen fibers showed better organization and orientation after BTX‐A injection. The histological changes observed after BTX‐A injection for facial wrinkles may help in better understanding of its mechanism of action.